Texture Profile Analysis Applied to Pounded Yam - Otegbayo, B.; Aina, J.; Abbey, L.; Sakyi-Dawson, E.; Bokanga, Mpoko; Asiedu, R. (Journal of Texture Studies (38): 355-375, 2007)
Textural quality of pounded yam made from tubers of Dioscorea rotundata Poir. and Dioscorea alata L. that were freshly harvested or stored for 4 months were evaluated using texture profile analysis. Significant correlations were obtained between the values for texture attributes evaluated using sensory texture profile analysis and those from instrumental texture profile analysis (ITPA). This implies that ITPA had the ability to measure the textural quality of pounded yam in a way similar to a trained sensory panel and could be used as an objective method to evaluate the textural quality of pounded yam.
Keywords: Dioscorea species; Pounded yam; Texture profile analysis; Textural quality; Yam